Prospective study of nosocomial fungal meningitis in children--report of 10 cases - Huttova, M; Kralinsky, K; Horn, J; Marinova, I; Iligova, K; Fric, J; Spanik, S; Filka, J; Uher, J; Kurak, J; Krcmery, V (Scandinavian journal of infectious diseases, 1998)
Within an 8-year period, 10 cases of fungal nosocomial meningitis in children 0-13 y old were prospectively identified, 3 caused by yeasts other than Candida spp. (Rhodotorula rubra, Aureobasidium mansoni, Clavispora lusitaniae) and 7 by Candida albicans. Seven patients survived. whereas 3 neonates with fungal meningitis (all due to C. albicans) died. Risk factors for fungal nosocomial meningitis included cancer (2 children), previous neurosurgery (2 children), cranial trauma (1 case) and prematurity with low birthweight (5 cases). All patients except 1 had received broad-spectrum antibiotics before onset of meningitis. In addition to yeasts, bacteria were isolated from CSF of 4 children. One child had additional fungaemia. Univariate analysis was used to compare 10 cases of fungal to 91 cases of bacterial nosocomial meningitis. Except for concurrent bacteraemia, (60 vs 25.3%, P < 0.03), which was more frequently observed among fungal meningitis, there were no significant differences in risk factors, sequelae or outcome (mortality) between patients with fungal vs bacterial meningitis. A review of fungal meningitis reported within the last 20 y is included.
Keywords: fatální výsledek; Infant; Humans; kojenec; dítě; Child; Female; rizikové faktory; Prospective Studies; lidé; infekce spojené se zdravotní péčí; fungální meningitida; předškolní dítě; Meningitis, Fungal; ženské pohlaví; Male; Adolescent; Fatal Outcome; mužské pohlaví; prospektivní studie; Child, Preschool; mladiství; Risk Factors; Cross Infection